Live Feeds Used in the Larval Culture of Red Cusk Eel, Genypterus chilensis, Carry High Levels of Antimicrobial-Resistant Bacteria and Antibiotic-Resistance Genes (ARGs) - Luz Hurtado; Claudio D. Miranda; Rodrigo Rojas; Félix A. Godoy; Mark A. Añazco; Jaime Romero (Animals, 2020)
The culture of red cusk eel Genypterus chilensis is currently considered a priority for Chilean aquaculture but low larval survival rates have prompted the need for the continuous use of antibacterials. The main aim of this study was to evaluate the role of live feed as a source of antibacterial-resistant bacteria in a commercial culture of G. chilensis. Samples of rotifer and Artemia cultures used as live feed were collected during the larval growth period and culturable bacterial counts were performed using a spread plate method. Rotifer and Artemia cultures exhibited high levels of resistant bacteria (8.03 × 104 to 1.79 × 107 CFU/g and 1.47 × 106 to 3.50 × 108 CFU/g, respectively). Sixty-five florfenicol-resistant isolates were identified as Vibrio (81.5%) and Pseudoalteromonas (15.4%) using 16S rRNA gene sequence analysis. A high incidence of resistance to streptomycin (93.8%), oxytetracycline (89.2%), co-trimoxazole (84.6%), and kanamycin (73.8%) was exhibited by resistant isolates. A high proportion of isolates (76.9%) carried the florfenicol-resistance encoding genes floR and fexA, as well as plasmid DNA (75.0%). The high prevalence of multiresistant bacteria in live feed increases the incidence of the resistant microbiota in reared fish larvae, thus proper monitoring and management strategies for live feed cultures appear to be a priority for preventing future therapy failures in fish larval cultures.